(untitled) (Nigerian Journal of Technology, 2017)
The use of laterite, quarry dust and recycle aggregates etc as replacement for sand in sandcrete block production is common trend in developing countries like Nigeria. Most resources and research efforts are committed towards conducting trial test with a view to coming up with mix production that will yield the desired property. This work presents a mathematical model for predicting the compressive strength and water absorption of laterite-quarry dust cement block using augmented Scheffe’s simplex lattice design. The statistical models developed can predict the mix proportion that will yield the desired property. The models were tested for lack of fit and found to be adequate. http://dx.doi.org/10.4314/njt.v36i2.7